An integrated approach : holistic assessment of vocational trainees in the NZ dairy farming industry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Tertiary Education) at Massey University, Manawatu, New Zealand - Couper, Graeme William (Massey University, 2016)
Vocational training qualifications in New Zealand have undergone significant change since 2008 due to the Targeted Review of Qualifications (TRoQ) initiated by the New Zealand Qualifications Authority (NZQA). In 2016, Primary ITO introduced programmes for these new qualifications to the dairy farming sector. A new holistic assessment approach was implemented, centred on an integrated Evidence Portfolio. The purpose of this research was to: a) Compare the new assessment methodology with the previous approach, from the perspective of the Trainees, Employers, and Assessors, and: b) Determine the extent to which the new assessment approach enabled Learners to apply theoretical knowledge to practical workplace situations. While much research has been done about competency-based Vocational Education and Training (VET), it largely focusses on institution-based learners, not those who are based in the workplace. This research aimed to contribute to the literature by examining competency-based assessment in a post-TRoQ, New Zealand workplace-based context. The sample groups for this research were drawn from dairy farming trainees who were enrolled in the new qualifications, and had also achieved one of the previous qualifications. The employers and assessors of these trainees were also included. The research utilised semi-structured interviews with the participants to gain their views on the new assessment methodology and how it compared to the previous method. The findings of this research largely reinforce the literature on competency-based VET. A new contribution is made by examining competency-based VET in a workplace-based context. The new assessment methodology was successful in enabling trainees to apply their theoretical knowledge to practical workplace situations and it was preferred by the participants over the previous assessment method. It is concluded that the notion of how competence is viewed in a New Zealand VET context should be revisited, and that it could assume a wider focus. This research also highlights the link between underpinning theoretical knowledge and practical workplace performance and suggests that performance of practical workplace tasks could provide sufficient evidence to assess Trainees’ theoretical knowledge in the final stages of their qualification.
Keywords: Dairy farming employees; In-service training; Rating of; Dairy farming; Study and teaching; New Zealand